Impact of IL6R genetic variants on treatment efficacy and toxicity response to sarilumab in rheumatoid arthritis - Luis Sainz; Pau Riera; Patricia Moya; Sara Bernal; Jordi Casademont; Cesar Díaz-Torné; Ana Milena Millán; Hye Sang Park; Adriana Lasa; Hector Corominas (Arthritis Research & Therapy, 2023)
Abstract Background Sarilumab, an IL-6 receptor antagonist, is a first-line biologic disease-modifying anti-rheumatic drug for rheumatoid arthritis. The identification of genetic biomarkers as predictors of response to sarilumab could allow for a personalized treatment strategy to improve clinical outcomes. Methods We conducted a retrospective cohort study of 62 patients treated with sarilumab to determine whether single-nucleotide polymorphisms (SNP) in the IL6R gene could predict efficacy and toxicity responses. Six SNPs previously described in the IL6R gene (rs12083537, rs11265618, rs4329505, rs2228145, rs4537545, and rs4845625) were genotyped in DNA samples obtained from these patients. Using parametric tests, we evaluated the association between these polymorphisms and clinicopathological features. Treatment response was assessed six months after treatment initiation. Satisfactory response was based on EULAR criteria. Low disease activity was determined according to DAS28 and CDAI and quantitative improvements in DAS28 and CDAI scores. Results Three SNPs (rs4845625, rs4329505 and rs11265618) were significantly associated with response outcomes. All of the SNPs, except for rs12083537, had at least one significant association with dyslipidemia or hepatotoxicity. Conclusions These findings support the potential clinical value of SNPs, particularly rs4845625, as potentially useful biomarkers to predict response to sarilumab in patients with RA.